Методи вимірювання параметрів навколишнього природного середовища - Яцишин, А. В.; Попов, О. О.; Артемчук, В. О. (НТУ "ХПІ", 2014)
В статті виконано аналіз кількісних методів вимірювання параметрів навколишнього природного середовища, до яких відносяться хімічні, фізико-хімічні, фізичні та біологічні методи. Здійснено класифікацію кожного із зазначених методів кількісного аналізу. Визначені умови та межі застосування даних методів. Показано їх основні переваги та недоліки.

This paper reviews the quantitative methods of measuring the parameters of the environment. Their classification is presented and defined their main advantages and disadvantages. On the basis of the measured parameters measurement methods are divided into chemical, physico-chemical, physical and biological. Chemical methods rely on the use of chemical reactions to determine the composition of the system. The chemical methods include gravimetric and volumetric methods of measurement. Physico-chemical methods are based on the dependence of the physical properties of the chemical composition of the analyzed medium. These include optical, photometric, electrochemical and chromatographic measurement methods. Physical methods is determined by the property, which depends on the nature of the atoms and their concentration in the system. The physical methods include spectral analysis, radiometric techniques, a luminescence method, a method of nuclear magnetic resonance. The basis of the biological and biochemical research methods are the reaction of plants, animals and micro-organisms to the action of a particular factor.
Methods for measuring environmental parameters
Keywords: кількісний аналіз; біологічні методи; НПС; quantitative analysis; method for measuring; parameter; environmental